Deciphering the mechanisms of long non-coding RNAs in ferroptosis: insights into its clinical significance in cancer progression and immunology - Shengming Ou; Xiaoya Nie; Xiangyu Qiu; Xin Jin; Geyan Wu; Rongxin Zhang; Jinrong Zhu (Cell Death Discovery)
Abstract A new type of nonapoptotic, iron-dependent cell death induced by lipid peroxidation is known as ferroptosis. Numerous pathological processes, including inflammation and cancer, have been demonstrated to be influenced by changes in the ferroptosis-regulating network. Long non-coding RNAs (LncRNAs) are a group of functional RNA molecules that are not translated into proteins, which can regulate gene expression in various manners. An increasing number of studies have shown that lncRNAs can interfere with the progression of ferroptosis by modulating ferroptosis-related genes directly or indirectly. Despite evidence implicating lncRNAs in cancer and inflammation, studies on their mechanisms and therapeutic potential remain scarce. We investigate the mechanisms of lncRNA-mediated regulation of inflammation and cancer immunity, assessing the feasibility and challenges of lncRNAs as therapeutic targets in these conditions.